Peningkatan Nilai Tambah Limbah Ikan Sebagai Bahan Pangan Dan Pakan - Subkhan Riza; Syahrul (Jurnal Kebijakan Pembangunan dan Inovasi, 2017)
Catfish processing industry generally leaves waste products in the form of solid waste, such as bone, intestines (viscera), tethered meatand belly fat.The resulting wastes range from 20% - 60%, meaning there are about 4.8 tons - 14.4 tons of solid waste is produced by the catfish processing industry in Sentra Pengolahan Pascapanen Kampar, Kampar regency.The resulting solid waste will have a negative impact on the environment if there is no good and proper handling. This study aims to utilize catfish waste into value-added products as raw materials for food and feed. This research is done by experimental method. Production of processed catfish in Kampar regency of 382.97 tons consists of smoked fish, fish fillet, salted fish and derivatives such as abon, meatballs, nuggets, and crackers.Potential waste of catfish fillet that can be utilized are: fish bone 35%, abdominal fat 7%, tethered meat6% and offal 11%. The processing of solid waste byproducts of fish processing produces raw materials of amino acid are rich in amino acids, bone meal is rich in calcium, flour has rich protein content and fish oil is rich in omega-9.Protein content of fish meal starch 57,68%, flour 60,21%, and bone meal 12,08%. Value added production of 50 kg bone meal of Rp 200,000, - with a profit rate of 33%. Value added production of 30 kg of edible flour by Rp 75.000.- with a profit rate of 25%. Value added production of 10 kg fish meal for Rp 140.000. with a profit rate of 56%.